Technology and Finance - Ilyina, Anna.; Samaniego, Roberto (Washington, D.C. : International Monetary Fund, 2008)
The benefits from financial development are known to vary across industries. However, no systematic effort has been made to determine the technological characteristics that are shared by industries that tend to grow relatively faster in more financially developed countries. This paper explores a range of technological characteristics that might underpin differences across industries in the need or the ability to raise external funding. The main finding is that industries that grow faster in more financially developed countries tend to display greater R and D intensity or investment lumpiness, indicating that well-functioning financial markets direct resources towards industries that grow by performing R and D.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet